Think-Pair-Share for Novice English Readers: Engaging Seventh Graders to Explore Narrative Text - Binti Roifatus Siam; Rohmani Nur Indah (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2021)
Many studies have discussed the Think-Pair-Share strategy to increase students' learning motivation in various scientific fields, especially in learning English. However, it still requires more exploration concerning TPS implementation for seventh-grader students to improve their proficiency when engaged in narrative reading. This research departs from the student's opinion about the struggle to read and understand the narrative text, and the class was so boring. Therefore, it is assumed that the use of TPS can increase the student’s motivation in reading narrative text. The design chosen is classroom action research (CAR) implemented at MTs. Darul Hikmah Jabon. The participants were 26 students. This research is done with one pre-cycle for need analysis and two cycles to see the increase of the student's score. In the pre-cycle, only three students reached the success criteria. In the first cycle, the scores did not significantly increase; only eleven students succeeded. In the second cycle, twenty-three students showed improvement. It resumed that the TPS technique is very effective for increasing student motivation on reading narrative text. Keywords: Think-Pair-Share, Narrative Text, Classroom Action Research.